PERAN BABINSA KORAMIL 0811/09 DALAM MENINGKATKAN NILAI BELA NEGARA SISWA SMK JATIROGO MELALUI PELATIHAN BARIS BERBARIS - Darmoko; Hanry Putrantono, Asep; Supriyono, Tjatur Supriyono (PPM Sdirjianbang Akademi Militer, 2025)
Vocational High School is a formal educational institution whose mission is to prepare Indonesia's young generation who have the qualifications and skills according to the needs of the business and industrial world. In the current era of development of information technology, it has such a big impact on aspects of human life, including the field of education. One of the education sectors that has not escaped this impact is the Vocational High School (SMK). This study aims to describe the role of Babinsa Koramil 0811/09 in increasing the state defense value of SMK N Jatirogo students. This study uses qualitative research with a case study approach. The research subjects were all grade 1 students of SMK N Jatirogo. This research is a qualitative descriptive study. The results of the study stated that marching training can shape the character of SMK N Jatirogo students who are 1) Disciplined and orderly. 2) Have a leadership spirit. 3) Have a sense of cooperation. 4) Physically healthy. 5) Independent and have a sense of love for the motherland and are aware of defending the country.